PHRASE THEORY: PHRASE TYPES AND SUBTYPES: COORDINATE, SUBORDINATE AND PREDICATIVE PHRASES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article on "Phrase Theory: Phrase Types and Subtypes—Coordinate, Subordinate, and Predicative Phrases" provides a comprehensive overview of key syntactic structures used in sentence construction. It explores three primary types of phrases—coordinate, subordinate, and predicative—detailing their functions, structures, and various subtypes. The article explains how coordinate phrases link equal elements, subordinate phrases introduce dependent information, and predicative phrases describe or qualify the subject. Through clear examples, the text demonstrates how each phrase type operates within a sentence and contributes to meaning. It also highlights the distinctions between these phrase types, offering a thorough understanding of their roles in syntax. This resource is valuable for students of linguistics, language learners, and anyone interested in deepening their understanding of how phrases form the foundation of language structure.